Educação em saúde para crianças diabéticas por meio de cartilha educativa e abordagem lúdica - Hermes, Thaís Schmidt Vitali (2017)
Diabetes mellitus is a disease that is gradually evolving. Constant monitoring is required and in order to achieve that, medication with high costs needs to be purchased. This disease is a common public health issue, with childhood prevalence of Type 1 Diabetes Mellitus. Having sufficient control over the disease, isolation of the treatment alone isn't enough, that is necessary and adequate treatment because it will change the child’s daily life. The orientation adequate for those children and their families is by applying a strategy involving a health team that could prevent or decrease the risk of any complication that can appear with this disease. The objective is to describe the percussions of health education set to children with type 1 diabetes mellitus in relation to how to control this disease and how it can change the eating habits and sport practice. Demonstrate how to increase the glycemic indexes by the education books. The study was conducted with children between the age ranges of 8 to 12 years, they were accompanied by their family in a university hospital. The data collection consisted of applying structured formulary and it was divided into 3 parts. The first part is about the sociodemographic profile; the second is about any difficulties in controlling diabetes mellitus faced by the children or their families; and the last part is regarding the data collected from biochemical tests (fasting blood glucose and glaciated hemoglobin) obtained from medical charts and was updated weekly by the capilar glycemic from the child's registration map. After all children filled out a form, a group meeting was scheduled where they had a dynamic presentation and each participant explained what they know about diabetes mellitus. After that, they had six more meetings in a period of 90 days between February and April 2017. When the intervention was finished, one more formulary was applied to collect data in a period of 180 days to record more glycemic results. Thematic content analysis was used to obtain the results, which are presented in three thematic categories: Children and families in the experience of Diabetes Mellitus type 1; Type 1 diabetic child and family life; and Health education in the management of type 1 Diabetes Mellitus in childhood. It was observed that the children show more knowledge about diabetes mellitus (definition, symptoms, self-care and adequate insulin application and glycosometer handling). Resistance towards adapting to healthy eating habits that were advised was observed. The relationship between eating habits and bad glycemic control was shed a light upon. Fasting glycemia and HbAc decreased in some children at 90 days and increased again in 180 days, not being able to relate the activities with the obtained results. The study concluded that health education with the use of playbook and directions given to children with Type 1 Diabetes Mellitus is a tool that should be explored and used in the assistance practice of the interdisciplinary team, in order to contribute to the quality of life of these children.